Community based seasonally water quality testing of tributaries of Dehradun - Sharma, Brij M.; Singhal, Parul; Uniyal, Neeraj; T. Mourya, Ram; Sharma, Jai (The Scientific Temper, 2024)
The objective of the research was to assess the water quality of the Suswa river. Nine locations from the Suswa river of Dehradun were chosen for sampling. The research was carried out between 2020 and 2021. Physical and chemical parameters were analyzed by using different instruments. Turbidity (2-115 NTU), total dissolved solids (30-276 mg L-1), pH (7.58– 7.88), dissolved oxygen (6.04–10.32 mg L-1), hardness (124–198 mg L-1), alkalinity (40–84.6 mg L-1), nitrate (0.058–0.115 mg L-1), and phosphate (0.015–0.080 mg L-1) were among the significant parameters that were measured. The Suswa river water requires precautionary measures before use in order to prevent adverse health impacts on humans, as evidenced by the analysis of water samples obtained from several study locations around the study region. As a result, we need to keep an eye on the resources. Monitoring of the river’s geomorphic, environmental, and climatic changes should be done more often, and the results should be made public.